Investigating the Factors that Drive the Success of Halal Cloud Kitchen in Bangladesh - Ahmed, Rafiuddin; Alam, Muhammad Intisar; Sultana, Maria; Jim, Mahafizur Rahman (Universitas Muhammadiyah Surakarta, 2024)
With the integration of new technologies, various industries, including the food sector, are experiencing significant transformations. The emergence of Cloud Kitchens represents a notable technological shift within the food industry. This research endeavors to uncover the key factors contributing to the success of the Halal Cloud Kitchen sector in Bangladesh. To achieve this, a structured survey questionnaire was designed and distributed through Google Forms. Three hundred twenty-three responses were gathered using the snowball sampling method and utilized in hypothesis testing employing multiple linear regression. The findings indicate that, among the six variables considered,food quality, packaging, and discounts substantially influence the prosperity of Halal Cloud Kitchens. In contrast,the remaining variables were found to be insignificant. Finally,this study analyzes critical success criteria for Halal Cloud Kitchens in Bangladesh, highlighting food quality, innovative packaging, and strategic discounts. It provides practical suggestions for improving business efficiency and competitiveness, identifying limitations, and suggesting future research areas.